Neuropsychological approach to problem of human aggression under the conditions of modern society - Tkach, Bogdan (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2017)
The article is concerned with the analysis of manifestations of human aggression that is based on neuropsychological approach. The author has attempted to carry out a directive clustering of manifestations of human aggression, which includes anthropological, sociological and psychological aspects. It is allowed to define the spheres and limits of professional competence in the prevention and control of aggression. The constructive and destructive importance of aggression for society were explained. Genetic impressionability to the formation of aggressiveness to the destructive environment was shown. The paper describes psychological differences of manifestations of aggression in case of injury in parts of the prefrontal cortex, anterior tsynhulyar cortex, hippocampus, amygdales. Tendencies and trends of aggression in modern society are highlighted.